Impacto da deleção oócito-específica de Rad51 sobre o DNA mitocondrial e a divisão meiótica em murinos - Grejo, Mateus Priolo (Universidade Federal de São Carlos, 2020)
RAD51 is a protein of eukaryotic organisms, with a central role in the DNA repair pathway by homologous recombination. Its function in the nucleus of somatic cells is well established, being necessary for the maintenance of the cell cycle. RAD51 is also imported into the mitochondria, where it plays an important role in the replication of mitochondrial DNA (mtDNA) under conditions of replicative and oxidative stress. RAD51 is essential for initial embryogenesis, however, little is known about its function in the oocyte. Considering the importance of homologous recombination during meiosis, we hypothesized that RAD51 is essential for the oocyte development. Regarding the mitochondria, since mtDNA is intensely replicated during oocyte growth, it is possible that RAD51 is also determinant for this organelle in the oocyte. In this sense, in the present study, we used an animal model with oocyte-specific deficiency of RAD51 to investigate the role of this recombinase during oogenesis. As a result, we found that RAD51 is expendable for oocyte growth and ovulation. This conclusion was supported by the ovulation of a normal amount of knockout oocytes (Rad51-/-), which presented an organization of the meiotic spindle comparable to that of wild type oocytes. Furthermore, there was no impact of RAD51 deficiency on the number of mtDNA copies in the oocyte. Despite this, analysis at the transcriptional and protein level confirmed the oocyte-specific deletion of RAD51. As a conclusion, we can state that RAD51 is dispensable during the final development of the oocyte, from the primary follicle to ovulation. Its deficiency alone does not result in any evident impact on meiotic progression or mtDNA stability.
Conditional knockout of Rad51 gene in murine oocytes and its effect on mitochondrial DNA amount and meiotic progression
Keywords: Rad51; mtDNA; Oócito; Meiose; Mitocôndria; Oocyte; Meiosis; Mitochondria; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR